Pengaruh Sistem Informasi Manajemen Dan Pelayanan Publik Terhadap Kinerja Pegawai Penerima Pendapatan Dikantor Sistem Administrasi Manunggal Satu Atap (SAMSAT) Aek Kanopan - Morapahu Pardomuan Siregar (Journal Economy and Currency Study (JECS), 2022)
Government organizations are large organizations that serve and accommodate all levels of society with applicable laws and regulations. Therefore, government organizations must have reliable and productive human resources by trying to improve the performance of employees. Performance is the result of work that can be achieved by employees or groups of employees in an organization, in accordance with their respective authorities and responsibilities in an effort to achieve organizational goals. Good performance is influenced by two things, namely management information systems and good public services. This Research Aims To Know The Influence Of Management Information System And Public Service To The Performance Of The Employee Revenue Receipt At The One-Stop Manunggal Administration System Office (Samsat) Aek Kanopan. This research approach uses an associative approach. The data collection method used a questionnaire/questionnaire which was distributed to all employees receiving income at the SAMSAT Aek Kanopan office which is located at Jl. Class of 66 Aek Kanopan, Kualuh Hulu District, North Labuhanbatu Regency. And the research sample was 36 employees. The research sample and Data Analysis Techniques in this study are the classical assumption test which includes the normality test, multicollinearity test, and heteroscedasticity test. In Data Analysis Techniques include multiple linear regression test, hypothesis testing, test the coefficient of determination (R2). The results showed that partially the Management Information System had a positive and significant effect on employee performance, public services had a positive and significant effect on employee performance, and simultaneously the management information system and public services had an effect on the performance of the employee revenue receipts at the one-stop single-stop administrative system office ( Samsat) Aek Kanopan.